e^2-2e-1=0,求e^2+1/e^2的值
举一反三
- 估计积分\(\int_2^0 { { e^ { { x^2} - x}}} dx\)的值为( )。(利用估值定理) A: \([ - 2{e^2}, - 2{e^{ - {1 \over 4}}}]\) B: \([ - 2{e^2}, - 2{e^ { { 1 \over 4}}}]\) C: \([2{e^2},2{e^{ - {1 \over 4}}}]\) D: \([2{e^2},2{e^ { { 1 \over 4}}}]\)
- 利用性质6(估值定理)估计积分\(\int_2^0 { { e^ { { x^2} - x}}} dx\)的值为( )。 A: \([ - 2{e^2}, - 2{e^{ - {1 \over 4}}}]\) B: \([ - 2{e^2}, - 2{e^ { { 1 \over 4}}}]\) C: \([2{e^2},2{e^{ - {1 \over 4}}}]\) D: \([2{e^2},2{e^ { { 1 \over 4}}}]\)
- 高分子溶解在良溶剂中,则( )。 A: χ1>1/2, Δμ1 E>0 B: χ1>1/2, Δμ1 E<0 C: χ1<1/2, Δμ1E>0, D: χ1<1/2, Δμ1 E<0
- 方程$(x^2+1)(y^2-1) + xy y' = 0$的通解为 A: $y^2 = C \frac{e^{-x^2}}{x^2}$ B: $y = C \frac{e^{-x^2}}{x^2}$ C: $y^2 = C \frac{e^{-x^2}}{x^2}+1$ D: $y=C \frac{e^{-x^2}}{x^2}+1$
- 求方程$y\frac{{{d}^{2}}y}{d{{x}^{2}}}-(\frac{dy}{dx})^{2}=0$的通解: A: $y={{C}_{1}}{{e}^{-{{C}_{2}}x}}$ B: $y={{C}_{1}}{{e}^{-{{C}_{2}}{{x}^{2}}}}$ C: $y={{C}_{1}}x{{e}^{-{{C}_{2}}{{x}^{2}}}}$ D: $y={{C}_{1}}{{e}^{{{C}_{2}}x}}$